High concentrations of anthocyanins in genuine cherry-juice of old local Austrian Prunus avium varieties. (15th April 2015) - Schüller, Elisabeth; Halbwirth, Heidi; Mikulic-Petkovsek, Maja; Slatnar, Ana; Veberic, Robert; Forneck, Astrid; Stich, Karl; Spornberger, Andreas
Highlights: Full characterisation of fruit quality parameters of nine sweet cherry varieties. Sweet cherry juices show a high anthocyanin concentration. Sweet cherry juices show a high antioxidant capacity. Austrian varieties are particularly suitable for the production of processed products. Selected variety with high antioxidant capacity is suitable for mechanical harvest. Abstract: Antioxidant activity and polyphenols were quantified in vapour-extracted juice of nine Austrian, partially endemic varieties of sweet cherry ( Prunus avium ): cv. 'Spätbraune von Purbach', cv. 'Early Rivers', cv. 'Joiser Einsiedekirsche', cv. 'Große Schwarze Knorpelkirsche' and four unidentified local varieties. Additionally the effect of storage was evaluated for six of the varieties. A variety showing the highest antioxidant capacity (9.64 μmol Trolox equivalents per mL), total polyphenols (2747 mg/L) and total cyanidins (1085 mg/L) was suitable for mechanical harvest and its juice did not show any losses of antioxidant capacity and total anthocyanin concentration during storage. The juice of cv. 'Große Schwarze Knorpelkirsche' had also high concentrations of total anthocyanins (873 mg/L), but showed substantial losses through storage. The local Austrian sweet cherry varieties from the Pannonian climate zone are particularly suitable for the production of processed products like cherry juice with high content of anthocyanins and polyphenols.